New visions in respiratory allergy (asthma and allergic rhinitis): an iPAC summary and future trends - Papadopoulos, N. G.; Borres, M.; Gern, J.; Nieto, A. (Pediatr Allergy Immunol, 2008)
In many aspects, respiratory allergies, i.e., allergic asthma and rhinitis, represent the hallmarks of allergy. Epidemiologic data highlight their large prevalence of most parts of the world, socioeconomic analysis reveal their large impact on global health and the large number of scientific publications in this field regularly brings to light many new aspects of these diseases. However, the current understanding of respiratory allergies, in particular in children remains scarce. How can we efficiently prevent respiratory allergies in allergy-prone infants? How can we prevent the progression of the disease? What therapeutic strategies could efficiently address efficient immunomodulation? the international Pediatric Allergy and Asthma Consortium, addressed these issues by a thorough review of the literature providing a state-of-the-art current knowledge in respiratory allergy, and identified a series of needs to be addressed in future studies.
Keywords: Allergic; Asthma Diagnosis; Differential Disease Progression Humans Prevalence Rhinitis; Perennial Rhinitis; Seasonal World Health